Pengaruh Likuiditas Terhadap Laba Perusahaan Pada PT Bukit Asam Tbk - Octavia, Vrisca; Wulan, Maura (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This research aims to analyze the effect of liquidity on company profits at PT Bukit Asam Tbk. Liquidity is a company's ability to fulfill its short-term obligations, which is measured through financial ratios such as Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (CR). Company profits are the main indicator in measuring a company's financial performance. By using secondary data in the form of the annual financial report of PT Bukit Asam Tbk in a certain period, this research adopts a quantitative method with simple linear regression analysis to identify the effect of liquidity on company profits. The research results show that liquidity has a significant influence on company profits. Current Ratio (CR) and Cash Ratio (CR) make a greater contribution than Quick Ratio (QR) in influencing company profits. This shows that the company's ability to maintain cash and other current assets has a positive impact on increasing profits. These findings indicate that effective liquidity management can increase company profitability. Therefore, PT Bukit Asam Tbk is advised to continue to strengthen liquidity management in order to optimize its financial performance